Motor imagery and its effect on complex regional pain syndrome: an integrative review - Nélio Silva de Souza; Ana Carolina Gomes Martins; Victor Hugo do Vale Bastos; Marco Orsini; Marco Antônio A. Leite; Silmar Teixeira; Bruna Velasques; Pedro Ribeiro; Juliana Bittencourt; André Palma da Cunha Matta; Pedro Moreira Filho (Neurology International, 2015)
The motor imagery (MI) has been proposed as a treatment in the complex regional pain syndrome type 1 (CRPS-1), since it seems to promote a brain reorganization effect on sensory- motor areas of pain perception. The aim of this paper is to investigate, through an integrative critical review, the influence of MI on the CRPS-1, correlating their evidence to clinical practice. Research in PEDro, Medline, Bireme and Google Scholar databases was conducted. Nine randomized controlled trials (level 2), 1 non-controlled clinical study (level 3), 1 case study (level 4), 1 systematic review (level 1), 2 review articles and 1 comment (level 5) were found. We can conclude that MI has shown effect in reducing pain and functionality that remains after 6 months of treatment. However, the difference between the MI strategies for CRPS-1 is unknown as well as the intensity of mental stress influences the painful response or effect of MI or other peripheral neuropathies.